PENGARUH POLA KEPEMIMPINAN KEPALA SEKOLAH, PELATIHAN BERKELANJUTAN, MOTIVASI KERJA TERHADAP KINERJA GURU SMA SE KECAMATAN PALMERAH - Indera Setya Budiman; Ersam Mahendrawan; Lili Nurlaili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of the principal's leadership pattern, continuous professional development, and work motivation on teacher performance in senior high schools throughout Palmerah District. The study employed a quantitative approach using a survey method. The research population consisted of 161 teachers, with a sample of 115 respondents determined using the Slovin formula. Data were collected through a Likert-scale questionnaire that had met the validity and reliability requirements. Data analysis was conducted using descriptive statistics, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS software. The results indicate that the principal's leadership pattern has a positive and significant effect on teacher performance, with a regression coefficient of 0.294, a t-value of 2.804, and a significance value of 0.006 (< 0.05). Continuous professional development also has a positive and significant effect on teacher performance, with a regression coefficient of 0.100, a t-value of 0.767, and a significance value of 0.005 (< 0.05). Furthermore, work motivation has a positive and significant effect on teacher performance, with a regression coefficient of 0.036, a t-value of 0.704, and a significance value of 0.003 (< 0.05). Simultaneously, the principal's leadership pattern, continuous professional development, and work motivation have a positive and significant effect on teacher performance, as indicated by an F-value of 5.643 and a significance value of 0.001 (< 0.05). The coefficient of determination (R²) of 0.670 indicates that 67.0% of the variance in teacher performance can be explained by the three independent variables, while the remaining 33.0% is influenced by other factors outside the research model. These findings suggest that improving the principal's leadership pattern, implementing continuous professional development programs, and strengthening teachers' work motivation are essential strategies for enhancing teacher performance.